People-powered data collaboratives: fueling data science with the health-related experiences of individuals - Evans, Barbara J (J Am Med Inform Assoc, 2018)
The creation of people-driven data collaboratives, with governance structures that enable participants to have a meaningful voice in issues surrounding the use of their own data, is a novel strategy to harness our growing capacity to develop and maintain immense data assets from the real health experiences of individuals.